Preclinical multi-target strategies for myocardial ischemia-reperfusion injury - Li, Yuqing; Gao, Yi; Li, Guangping (Frontiers in Cardiovascular Medicine, 2022)
Despite promising breakthroughs in diagnosing and treating acute coronary syndromes, cardiovascular disease's high global mortality rate remains indisputable. Nearly half of these patients died of ischemic heart disease. Cardiomyocyte necrosis and apoptosis account for most cell death in ischemic heart disease. Primary percutaneous coronary intervention (PCI) and coronary artery bypass grafting can rapidly restore interrupted blood flow and become the most effective method for salvaging viable myocardium. However, restoring blood flow could increase the risk of other complications and myocardial cell death attributed to myocardial ischemia-reperfusion injury (IRI). With studies of the mechanism of myocardial IRI, more therapeutic targets and drug candidates have been forced. In preclinical experiments, many treatments have substantial cardioprotective effects against myocardial IRI. However, the transition from these cardioprotective therapies to clinically beneficial therapies for patients with acute myocardial infarction remains elusive. Its clinical trial results were disappointing. One important reason is the complex pathophysiological mechanism of myocardial IRI as well as patients' comorbidities so that the effect of a single drug is not enough to cause sufficient myocardial protection. Emerging research suggests that the optimal cardioprotective strategy may require the combination of additive or synergistic multitarget therapies. This review will provide an overview of today's cardioprotection challenges and a taxonomy of cardioprotection strategies to describe the pathophysiological mechanism of myocardial IRI. We propose a prospective multi-target drug combination for myocardial IRI with the latest research progress in preclinical experiments and contribute to clinical trials further.